2019
DOI: 10.1063/1.5099272
|View full text |Cite
|
Sign up to set email alerts
|

AC electrokinetic induced non-Newtonian electrothermal blood flow in 3D microfluidic biosensor with ring electrodes for point-of-care diagnostics

Abstract: Defect-rich GaN interlayer facilitating the annihilation of threading dislocations in polar GaN crystals grown on (0001)-oriented sapphire substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To validate the CUDA Fortran code for rheological behavior of non-Newtonian flow, the power-law-based Poiseuille flow is simulated and compared with analytical solutions in our previous published work [17]. With parallel GPU acceleration, the computational speed of the LBM solver is improved by more than 400 times (100 × 100 × 100 nodes) compared with serial simulation using a single CPU thread [17].…”
Section: Cuda Fortran Code Calibrationmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate the CUDA Fortran code for rheological behavior of non-Newtonian flow, the power-law-based Poiseuille flow is simulated and compared with analytical solutions in our previous published work [17]. With parallel GPU acceleration, the computational speed of the LBM solver is improved by more than 400 times (100 × 100 × 100 nodes) compared with serial simulation using a single CPU thread [17].…”
Section: Cuda Fortran Code Calibrationmentioning
confidence: 99%
“…As the ACET flow is a multi-physical phenomenon, its velocity magnitude simultaneously depends on the accuracy of LBM solvers for electric potential, temperature field, and fluid flow. Under this circumstance, to validate the LBM solvers for these multi-physical fields, the vertical Stokes drag force F sty on a suspended particle in ACET flow is calculated [17] and quantitatively compared with the results in Cao et al [53] through setting the same parametric parameters, computational domain geometry, and boundary conditions. As displayed in figure 2, the results computed from the current CUDA Fortran code are consistent with those in reference [53], which validates the accuracy of our LBM solvers.…”
Section: Cuda Fortran Code Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hong et al developed a coupled model, compared it with the classical model, and found that only at small temperature rises do the results of the two models match [87]. More recently, pumping and mixing of non-Newtonian fluids have been studied [89,90,91].…”
Section: Theorymentioning
confidence: 99%